Analisis Autokorelasi Spasial: Studi Kasus Pembangunan Sekolah dan Kepadatan Penduduk di Wilayah Sumatera Utara - Hondro, Yizhar Saputra; Triono, Wira; Panjaitan, Rizky Rafiza (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study uses a quantitative approach that examines the development of schools, especially elementary schools, towards population density in the North Sumatra region using the Moran's I and LISA methods. Defining spatial autocorrelation as the relationship between the closest spatial units as seen on the map, and based on the results of the analysis, 4 regions were obtained for the number of residents that significantly influenced autocorrelation, including Deli Serdang (p-value = 0.0004), Karo (p-value = 0.0086), Medan (p-value = 0.00001), and Binjai (p-value = 0.0028). In addition, for the number of elementary schools, 7 regions were obtained that significantly influenced autocorrelation, namely Batu Bara (0.0371), Deli Serdang (p-value = 0.0003), Karo (p-value = 0.0006), Binjai (p-value = 0.0015), Medan (p-value = 0.0009), Pematangsiantar (p-value = 0.0279), and Sedang Berdagai (p-value = 0.0310). These regions have p-values less than 0.05 so it can be concluded that these regions significantly influence spatial autocorrelation.